Effects of annealing temperature towards surface morphological and optical properties of black silicon fabricated by silver-assisted chemical etching. (1st March 2019) - Md. Noor, Nur Afidah; Mohamad, Siti Khadijah; Hamil, Siti Sarah; Devarajan, Mutharasu; Pakhuruddin, Mohd Zamir
Abstract: This paper presents investigation on the effects of annealing temperature towards surface morphological and optical properties of black silicon (b-Si) fabricated by a two-step silver-assisted chemical etching process. Crystalline (c-Si) wafers are deposited with a thin film silver (Ag) layer. The c-Si wafers are annealed in nitrogen atmosphere for 40 min at different temperatures (200–260 ℃) to form Ag nanoparticles. The wafers are then etched in the aqueous solution of HF:H2 O2 :DI H2 O at room temperature for 70 s. The results show that the surface morphologies of all samples are rough due to the presence of b-Si nanotextures. The b-Si wafers demonstrate significantly lower broadband reflection compared to the planar reference. The b-Si wafer annealed at 230 ℃ demonstrates the lowest reflection (3%) and highest absorption (97%) at the wavelength of 600 nm. This sample exhibits b-Si nanotextures with average width less than 50 nm and height of 245 nm. The enhanced broadband light absorption in the best b-Si wafer gives the highest maximum potential short-circuit current density (Jsc(max) ) of 39.6 mA/cm 2, or enhancement 50.6% compared to the planar c-Si reference wafer, calculated for wavelength region of 300–1100 nm.